Answer:
I don't see the equation for the line, but I describe the process.
Explanation:
Let's look for a line that has the form y=mx+b, where m is the slope and b the y-intercept (the value of y when x=0).
The slope of a perpendicular line is the negative inverse of the slope of the reference line. In this case the equation for the reference line is missing. If it is in the form y=mx+b, take the m value, invert it, and then give it a "-" sign. For example, if the line is y = 2x +1, the negative inverse of the slope of 2 would be -(1/2).
The new line will have this new slope [-(1/m)] to make it y = -(1/m)x + b.
To find b, use the given point of (3,-2) in the equation and solve for b:
y = -(1/m)x + b
-2 = -(1/m)*(3) + b
Then solve for b and you'll have the equation for the solution to the problem.